Variation in oxidative defense system and physiological traits in Maize under drought stress - Shahimoghadam, Monireh; Asghari, Ali; Moharramnejad, Sajjad; Dehghanian, Zahra; Singh, Sandeep Kumar; Sivalingam, Krishna Moorthy; Marisennayya, Senapathy (Plant Science Today, 2024)
The study included the role of key metabolites involved in oxidative defense, and osmotic adjustment under water stress is still undiscovered. We have evaluated whether antioxidant potential could be nominated as a potential marker of drought resistance in three maize hybrids (SC01, SC703, and SC720). Underwater deficiency in all maize hybrids decreased significantly compared to control samples in grain yield, photosynthetic pigments, and phenolic compounds. In contrast, proline and glycine betaine (GB) significantly increased. In contrast, a significant increase (p<?0.05) was detected in the lipid peroxidation indicator of malondialdehyde (MDA). The hydrogen peroxide (H2O2) and total soluble proteins remained unaffected under drought stress in the three maize hybrids. Electrophoretic investigations attributed three, two, and one isoforms, respectively, to peroxidase (POX), superoxide dismutase (SOD), and catalase (CAT). In the studied maize hybrids, SOD isoforms, including Fe-SOD, Cu/Zn-SOD, and Mn-SOD, appeared on the 8% slab polyacrylamide gels. The water stress decreases Mn-SOD, Cu/Zn-SOD, and Fe-SOD activities in all three hybrids. Further, POX1, POX2, and CAT activities decreased in SC01 and SC703, while they increased in SC720 under water deficit stress. In all maize hybrids, oxidative stress from water limitation leads to significant changes in the enzymatic/non-enzymatic antioxidants and main organic osmolytes. Based on the current study's findings, we believe that Cu/Zn-SOD activity, proline, and photosynthetic pigments might be used as biochemical indicators of water stress tolerance.